Can Reptiles Use Nest Site Choice Behavior to Counter Global Warming Effects on Developing Embryos? Potential Climate Responses in a Turtle - Sullivan, Sean; Heinrich, George L.; Mattheus, Nichole M.; Cassill, Deby; Doody, J. Sean (Frontiers in Ecology and Evolution, 2022)
Climate warming is forecasted to cause extinctions, but populations can theoretically use adaptive evolution to avoid extinction in a rapidly changing environment (i.e., evolutionary rescue), precluding the need for intervention. Although strong links between a changing climate and the physiology of an organism are expected, those links can be buffered by behavior. Nest site choice behavior, for example, can reduce or eliminate environmental variation that would be experienced by embryos placed randomly with respect to environmental temperatures. We tested four provisions of this prediction by quantifying nest sites and ‘potential’ nest sites in the Florida softshell turtle (Apalone ferox). First, turtles chose nest sites with mean canopy openness values (32-47%) that were intermediate between the shadiest (14-17%) and the sunniest potential nest sites (36-57%) available. Second, canopy openness, incident radiation intensity, and nest temperatures were generally, positively related to one another, indicating definitive thermal consequences of nest site choice. Third, our study revealed ample, cooler nest sites available to turtle mothers within close proximity to nest sites utilized; by nesting in the most shaded sites, softshell turtle mothers could depress mean nest temperatures by ~2°C. Fourth, the growth of vegetative cover throughout incubation had negligible effects on canopy openness, incident radiation intensity, and nest temperatures, supporting the potential for mothers to ‘predict’ developmental temperatures using temperature cues during nest site choice. Finally, our data revealed considerable individual-level variation in canopy openness chosen by nesting mothers; such behavior could thus, be subject to natural selection via embryonic mortality under future warming. Collectively, our study suggests that Florida softshell turtles, and probably other turtle species nesting in relatively open areas, may be able to counter climate change effects on developing embryos by nesting in more shaded microhabitats, assuming nest site choice behavior is heritable and can evolve at a sufficient rate to keep pace with climate warming. The evolutionary and behavioral mechanisms (e.g., assessing substrate temperatures directly vs. indirect choice of canopy cover) in the repertoire of nesting mother turtles for responding to climate warming remain elusive and are required for a more complete understanding of climate responses.